A Study about Consumer Attitude towards Online Grocery Stores - Arora, Divya; Gupta, Sudipta Sen (Gyan Management Journal, 2022)
Online grocery shopping has grown rapidly over the past few years. The  purpose of this research is able to identify the concept of online grocery  stores and to understand how the consumer feels about purchasing  groceries from these online stores, also this paper is about determining the  elements that might encourage or oppose consumers to purchase groceries  from online stores. Basically, how consumers perceive online grocery stores.  The findings would emphasize consumer attitudes towards online grocery  stores and how online grocery shopping changes consumer behaviour and  shopping pattern.
Keywords: Online grocery stores; Consumer attitude; Consumer perception; Online shopping; Consumer behavior